Water and Wastewater Services in the Danube Region : Slovenia Country Note - World Bank (Washington, DC, 2015)
To evaluate and reflect the sustainability of services in the region, an overall sector sustainability assessment was done, taking into account four main dimensions: access to services, quality of services, efficiency of services, and financing of services. Each of these dimensions is measured through three simple and objective indicators. For each indicator, best practice values are established by looking at the best performers in the region, and countries closest to those best performers are deemed to have a more mature sector. A more complete description of the methodology to assess the sector sustainability is included in the annex of the state of the sector regional report from the Danube Water Program. The outcomes of this assessment for the Slovenia water sector are displayed, which also shows average and best practices in the Danube region. The Slovenian sector sustainability score is 84, which is above the Danube average sustainability score of 64. The assessment shows that, on average, the country performs well in terms of access to piped water and flush toilets, affordability, continuity of service, customer satisfaction, nonrevenue water, and collection ratio. The main deficiencies of Slovenia’s water sector identified through the sector sustainability assessment are wastewater treatment coverage, operating cost ratio, and investment level. The main sector challenges are: increasing the rehabilitation of the water infrastructure and improving its reliability; and improving monitoring and reporting practices.